2023
DOI: 10.1093/infdis/jiad166
|View full text |Cite
|
Sign up to set email alerts
|

The Type VI Secretion System Contributes to the Invasiveness of Liver Abscess Caused by Klebsiella pneumoniae

Abstract: Background Klebsiella pneumoniae liver abscess (KPLA) with extrahepatic migratory infections is defined as invasive KPLA (IKPLA). The type VI secretion system (T6SS) is involved in the pathogenesis of KPLA. We hypothesized that T6SS play a role in the IKPLA. Methods 16S rRNA gene sequencing was performed on abscess samples. Polymerase chain reaction (PCR) and reverse transcription (RT)-PCR was used to validate the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…[9] The type VI secretion system contributes to the invasiveness of liver abscess caused by K. pneumoniae. [10]. T2SS genes (gspE, gspF,gspG) were also identified in four isolates.…”
Section: Resultsmentioning
confidence: 93%
“…[9] The type VI secretion system contributes to the invasiveness of liver abscess caused by K. pneumoniae. [10]. T2SS genes (gspE, gspF,gspG) were also identified in four isolates.…”
Section: Resultsmentioning
confidence: 93%
“…Additionally, relative to cluster 1, cluster 2 strains had a distinct set of effector/immunity proteins from a T6SS (). T6SSs function as injection machinery that can directly puncture both eukaryotic and prokaryotic membranes, and have been identified as contributing to K. pneumoniae pulmonary infection, gastrointestinal colonization, bacterial competition and liver abscess formation [72–75]. Future work will be necessary to further functionally characterize potential differences in virulence and resistance factors contributing to each CG307 clades’ respective success.…”
Section: Discussionmentioning
confidence: 99%
“…We have established that K. pneumoniae T6SS targets not only other bacteria but also fungi and eukaryotic cells [26,27]. Furthermore, we and others have also demonstrated that the T6SS contributes to K. pneumoniae infection biology [15,[26][27][28][29][30]. Therefore, we asked whether the T6SS shapes the lung cellular environment, and whether the T6SS modulates the…”
Section: Type VI Secretion System Shapes the Atlas Of Lung Immune Cel...mentioning
confidence: 99%